Physicochemical, shear flow behaviour and emulsifying properties of Acaciacochliacantha and Acaciafarnesiana gums - Sibaja-Hernández, Roberto; Román-Guerrero, Angélica; Sepúlveda-Jiménez, Gabriela; Rodríguez-Monroy, Mario (Industrial crops and products, 2015)
[Display omitted] •Gums from Acaciafarnesiana and Acaciacochliacantha were examined.•Gum exudates were collected from wild Acacia trees growing in Mexico.•Gums show similar physicochemical properties to other Acacia gums.•Gums had high solubility, shear thinning behaviour and low apparent viscosity.•A. farnesiana gum has potential as emulsifier and source of dietary fibre. The physicochemical, shear flow behaviour and emulsifying properties of gum exudates from Acaciacochliacantha and Acaciafarnesiana were analysed and compared to those for Acaciasenegal gum. Evaluation of physicochemical properties showed that A. farnesiana and A. senegal gums displayed levorotatory activity, relatively high carbohydrate/protein ratio and high content of dietary fibre. Similarly, A. farnesiana and A. senegal gums formed stable oil-in-water emulsions with smaller droplet sizes and coalescence rates in the order of 10−8, meaning for very stable disperse systems. Otherwise, A. cochliacantha gum was the only with dextrorotatory activity, high content of protein and arabinogalactan-proteins (AGPs), but low carbohydrate fraction; nevertheless, despite the possible advantages of high protein content associated with emulsifying properties, this polysaccharide showed lesser stability on emulsions. These results indicate that there is correlation between emulsion stability and an adequate carbohydrate/protein balance in the gums; additionally of the AGPs presence. Thus, A. farnesiana gum may be considered for oil-in-water emulsion stabilization and sources of soluble dietary fibre due to their relatively high polysaccharide fraction.